Clinical profile of dilated cardiomyopathy in children enrolled in chronic cardiac care: a decade review in a sub-Saharan African tertiary center - Henock Gashaw; Henok Tadele (BMC Cardiovascular Disorders)
Abstract Background Dilated cardiomyopathy (DCM) is a myocardial disease characterized by a dilated left ventricle (LV) and reduced LV systolic function. The clinical profile of DCM is not well studied in Africa with no reports from Ethiopia. This study aimed to describe the clinical profile of DCM and the factors associated with its clinical outcome in a tertiary center. Results This study included 75 DCM patients, males 52%. The median age at DCM diagnosis was 18 months (Interquartile range/IQR: 7–46). The major DCM clinical presentations were cough, 84%, fast breathing, 64% and shortness of breath, 56%. The median left ventricular systolic ejection fraction (LVEF) and left ventricular fractional shortening (LVFS) at diagnosis were 30% (IQR: 24–36) and 14% (IQR: 11–18), respectively. The majority don’t have a cause labeled or documented, 81.3% while HIV and anthracycline-related DCM accounted for 6.7% each. Concerning outcomes, the majority didn’t show any clinical status change or were static, 62.7% while one-third, 32%, showed improvement. The case fatality rate in this series was 5.3% [4] (95% CI: 1.47–13.1). The presence of severe acute malnutrition (wasting) at presentation, p 0.017; the latest LV systolic function (LVEF, p 0.000 and LVFS, p 0.000) and the use of enalapril, p 0.017, were associated with DCM clinical outcome. Conclusion Boys in their second birth year were most affected by DCM. The major DCM presentations were a mix of respiratory and cardiac symptoms with severely depressed LV systolic function. Nutritional status at presentation, recent LV systolic function and enalapril use were associated with DCM clinical outcome. Timely nutritional assessment, treatment and support, and enhanced HF medical treatment are recommended to improve DCM clinical outcomes.